Correlation study of CAR, PLR, NLR with the prognosis of cardiogenic cerebral embolism patients - Xiaojing Du; Xiaohui Li; Sheng Yue; Yuzhen Sun; Mengzhen Zhao; Lingshan Zhou; Xingwei Wang; Yapan Yang (Experimental Biology and Medicine)
This study explored the association between inflammatory biomarkers—C-reactive protein to albumin ratio (CAR), platelet to lymphocyte ratio (PLR), and neutrophil to lymphocyte ratio (NLR)—and the prognosis of patients with cardiogenic cerebral embolism (CCE). We retrospectively analyzed data from 80 CCE patients diagnosed between June 2020 and June 2024, categorizing them into favorable and unfavorable prognosis groups based on outcomes such as death, recurrence, and disability. The CAR, PLR, and NLR values were calculated from routine blood tests, and statistical analyses, including Spearman correlation, multivariate logistic regression, and ROC curve analysis, were performed to examine their prognostic significance. Results showed that the unfavorable prognosis group had significantly higher CAR, PLR, and NLR values compared to the favorable group (P < 0.05). Spearman correlation analysis revealed positive associations between these biomarkers and prognosis (r = 0.319 for CAR, 0.238 for PLR, 0.251 for NLR, all P < 0.05). Multivariate analysis identified CAR and NLR as independent risk factors for unfavorable prognosis (OR = 1.034 for CAR, OR = 3.887 for NLR). ROC analysis determined optimal cutoff values for CAR (>0.74), PLR (>160.00), and NLR (>3.53) to predict unfavorable prognosis with AUCs of 0.796, 0.694, and 0.705, respectively. The combined biomarker test yielded an AUC of 0.899. Kaplan-Meier survival analysis indicated significantly lower survival rates for patients with higher levels of CAR, PLR, and NLR (P < 0.05). In conclusion, elevated CAR, PLR, and NLR are reliable indicators of a poor prognosis in CCE patients.